Atypical Patterns of Constrictive Pericarditis after Heart Transplantation: A Case Report - Ueda Nobuhiko; Seguchi Osamu; Kuroda Kensuke; Nakajima Seiko; Sato Takuma; Yanase Masanobu; Hata Hiroki; Fujita Tomoyuki; Kobayashi Junjiro; Fukushima Norihide; Nakatani Takeshi (Journal of Organ Transplantation, 2017)
Constrictive pericarditis (CP) represents a rare complication after heart transplantation (HTx), resulting from various postoperative events such as mediastinitis, pericardial effusion, or allograft rejection. We describe our recent experience with managing an HTx recipient who developed atypical patterns of CP predominantly involving the right ventricle. A 52-year-old male who had received heart transplantation 2.5 years before was admitted to our institution because of progressive symptoms of heart failure. The patient had experienced acute rejection twice post-HTx, both with International Society for Heart and Lung Transplantation grade 1R, undergoing an additional endomyocardial biopsy other than those performed during regular check-ups. On admission, echocardiography revealed paradoxical septal motion and a large cystic-like mass with a thick capsule in front of the right ventricle. Right heart catheterization revealed elevation of right atrial pressure, with severely reduced cardiac index. Magnetic resonance imaging revealed both seroma and a thick cystic-like capsule tightly adhered to the right ventricle. CP was suspected despite the atypical patterns of presentation. Seroma was removed through exploratory lateral thoracotomy, without improvement in symptoms, which was only achieved via subsequent pericardiectomy involving resection of the thickened parietal pericardium, removal of effusion fluid, and further excision of diffusely thickened visceral pericardium and epicardium. The patient is currently recovering uneventfully. The possibility of CP after HTx should be considered despite the rarity of this condition and HTx recipients should be closely monitored using various imaging modalities because CP typically demonstrates non-specific symptoms and physical findings of heart failure, with high mortality.
Keywords: Heart failure